Prevalence of adverse outcomes of pregnancy in Sivas-Turkey and their associated factors: A population-based survey - Naim Nur; Haldun Sumer (Tehran University of Medical Sciences, 2018)
Background & aim: Adverse pregnancy outcomes, including preterm birth (PTB) and low birth weight (LBW) are complications of complex etiology associated with newborn morbidity and mortality. The aims of this study were to explore smoking and other social factors associated with adverse pregnancy outcomes in women of childbearing ages Methods & Materials: The cross-sectional survey involved 1273 women were conducted in Sivas center, Turkey, between September 2013 and May 2014. Multiple linear regression models were performed to demonstrate the significant factors associated with preterm birth (PTB) and low birth weight (LBW). Results: Multivariate analysis significantly showed that having a low educational level (odds ratio, OR = 4.25 for PTB and OR = 4.93 for LBW), being unemployed (OR = 2.08 only for PTB), being a smoker (OR = 1.37 for PTB and OR = 1.67 for LBW), being a multiparous women (OR = 2.59 for PTB and OR = 3.79 for LBW) and having a low income level (OR = 1.53 only for LBW) were the factors associated with the PTB/LBW. Conclusion: Smoking as modifiable risk factors and other socio-economical factors should be addressed for the main goal of improving womens' health. From this point, health-promoting implementations are important to encourage and support women to stop smoking before or on early stage of their pregnancies especially in those lower educated and those from lower socio-economic conditions to reduce PTB and LBW. Keywords: Women; Pregnancy; Smoking; PTB; LBW